A Comparative Study of Options with Reference to ICICI Bank, SBI and Axis Bank - Ms. Susmitha; Ms. Sreyasree (Journal of Corporate Finance Management and Banking System, 2024)
Options trading is a dynamic and sophisticated field that shapes investment strategies for big banking organizations in the complex world of financial markets. With a focus on three major participants in the Indian banking industry—ICICI Bank, State Bank of India (SBI), and Axis Bank—this study conducts a thorough comparative analysis. The study aims to dissect and compare the complex tactics, positions in the market, and general performance of these banks in the field of options trading. It provides a thorough analysis of market positioning and competitiveness as well as deep insights into the complex strategies used by each bank. Additionally, it looks to pinpoint the crucial elements of success as well as the difficulties these financial organizations face in the intricate world of options trading. Insightful comparative studies, the discovery of original tactics, an assessment of market positioning, and comprehensive insights into the elements determining success or difficulties faced by ICICI Bank, SBI, and Axis Bank in the ever-changing world of options trading are among the anticipated results. For investors, financial analysts, and regulators who want to understand the intricacies of options trading in the banking industry, this might be a useful tool.